Jasa Pelayanan Bandara Halim Perdana Kusuma dan Bandara Husein Sastranegara - Andri, Andri; Kasim, Roswan; Wahyuni, Endang (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2016)
The study entitled âAnalysis Comparison of Satisfaction Passenger Against the Service Halim Perdana Kusuma Airport in Jakarta and Bandung Husein Sastranegara Airport in 2015â was conducted to determine and analyze the quality comparison service consisting of responsiveness, assurance, tangibles, empathy and reliability to consumer satisfaction on Hussein Airport Sastranegara and Halim Perdana Kusuma Airport. This study was conducted to determine and analyze the dominant service quality dimensions that influence satisfaction. The benefits of this research is to get a general idea about the services at Soekarno Hatta and Halim Perdana Kusuma Airport in Jakarta. To determine the level of satisfaction of passengers on each variable services at Bandung Husein Sastranegara Airport and Halim Perdana Kusuma Airport. Keywords : airport, satisfaction of passengers, service and performance